Environmental Sustainability Practices and Commitment in Ghanaian Hotels: A Comprehensive Review - Emilia Etsa Milla-Amekor (Geography, Earth Science and Environment: Research Highlights Vol. 10, 2025)
Ghana has witnessed substantial investment in its hotel business from both domestic and foreign enterprises. However, the environmental impact of the industry is exacerbated by the availability of additional amenities such as restaurants, nightclubs, shopping malls, swimming pools, parking lots, and golf courses, all of which contribute to indirect and induced environmental effects. Environmental initiatives and conversations have raised environmental sustainability consciousness among hotel consumers, prompting them to demand that the products and services they use be eco-friendly. The primary objective of this study is to investigate the commitment of hotels in Ghana to environmental sustainability. This study is a comprehensive review using online research journal websites online research journal websites, such as the PubMed database, Academic Library, and Google Scholar, as well as other in-context articles. This study focused on understanding environmental sustainability and examining its adoption and the level of commitment among hotels in Ghana. Hotel businesses engage in environmental management by developing environmental policies, green procurement, adhering to environmental legislation, environmental auditing, ecolabelling and certification, waste management and recycling, water and energy conservation, environmental education, pollution prevention, responsible marketing practices, and community support. Hotel managers are aware of the environmental issues that the tourism industry faces. They see their engagement in environmental management strategies as helping to reduce costs through operational efficiency. To further promote sustainability, hotels in Ghana should encourage energy-efficient equipment, renewable energy sources, and water-saving technologies. Additionally, educating employees about sustainable practices and involving visitors in environmental efforts can also help hotels improve their environmental responsibilities.